About Economy of Fuel at Thermal Power Stations due to Optimization of Utilization Diagram of Power-Generating Equipment - M. V. Svechko; V. E. Pitolin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Problems of rational fuel utilization becomes more and more significant especially for thermal power stations (TPS). Thermal power stations have complicated starting-up diagrams and utilization modes of their technological equipment. Method of diagram optimization of TPS equipment utilization modes has been developed. The method is based on computer analytical model with application of spline-approximation of power equipment characteristics. The method allows to economize fuel consumption at a rate of 15-20 % with accuracy of the predicted calculation not more than 0.25 %.